Content feature of medical crowdfunding information in social media—a content and effectiveness analysis of medical crowdfunding posts on Sina Weibo in China. - Cai, Yingying; Kamarudin, Syafila; Nujaimi, Saiful; Jiang, Xiaoyu; Zhang, Xin (Redfame Publishing Inc., 2024)
Attracting donations is challenging but imperative for fundraisers to secure donations. Solicitation narratives serve as a key strategy for attracting both acquaintances and strangers, thereby influencing donation behavior. To optimize medical crowdfunding messaging on social media, this study explores prevalent content features of medical crowdfunding messages on Sina Weibo and determines whether these features impact message effectiveness. A retrospective content analysis was conducted on medical crowdfunding posts on Sina Weibo in China throughout 2023. The posts were systematically coded for the author’s gender, author type, target audience, key themes, human imagery, message sentiments, and message strategies, with their effectiveness analyzed using SPSS. Out of the 394 posts analyzed, private authors emerged as the dominant voices, directing their appeals predominantly toward the general public and often expressing neutral to negative sentiments. The overarching theme across these posts centered on the dire need for medical assistance. Including human imagery and informative message strategies was pivotal in determining post-effectiveness, eliciting heightened audience engagement in terms of likes and shares. Negative sentiment posts influenced comment effectiveness. These findings underscore the potential of social media campaigns in promoting altruistic health behaviors while emphasizing the critical role of strategic message design through the use of human imagery, informative message strategies, and negative sentiment to improve audience engagement.